Unlocking Linguistic Brilliance: Elevating Ninth-Grade Vocabulary Proficiency through Strategic Word Lists at SMP Al-Azhar 3 Bandar Lampung - Suherni, Suherni; Damiri, Adenan; Nurchurifiani, Eva (IJLHE: International Journal of Language, Humanities, and Education, 2023)
This research aimed to improve students' vocabulary mastery through a word list. The research subjects were the ninth-grade students of SMP Al-Azhar 3 Bandar Lampung, consisting of 28 students. Classroom Action Research (CAR) was employed, comprising two cycles. Data collection techniques included both test and non-test methods. A vocabulary test was administered to assess students’ vocabulary mastery, while an observation sheet was used for non-test data. Data analysis involved both quantitative and qualitative methods. Referring to the test results, the mean score of students’ learning activities in cycle 1 was 6.42, categorizing as less active. Meanwhile, in cycle 2, it increased to 7.32, still considered less active, showing an improvement of 0.9%. On the other hand, the mean score of the vocabulary test in cycle 1 was 69.04, with 7 students scoring ≥70, constituting 25%. In cycle 2, the mean score rose to 76.16, with 21 students scoring ≥70, accounting for 75%. This indicated an improvement of 7.12%. Based on the research results, it can be concluded that a word list effectively improves students’ vocabulary mastery in the ninth grade of SMP Al-Azhar 3 Bandar Lampung.